THE IMPACT OF TAX POLICY ON THE INVESTMENT CLIMATE: A COMPARATIVE ANALYSIS OF DEVELOPING COUNTRIES (American Journal of Technology and Applied Sciences, 2025)
This article examines the impact of tax policy on the investment climate in developing countries. A comparative analysis of tax practices across various countries is provided, examining the mechanisms by which corporate tax rates and tax incentives influence foreign direct investment (FDI). Key factors determining the effectiveness of tax policy are identified, including the quality of administration, transparency, and institutional conditions.